Konsepsi Pendidikan Islam terhadap Prinsip multikultural - koko adya winata (Atta'dib Jurnal Pendidikan Agama Islam, 2020)
AbstractThis study aims to examine how the conception of Islamic education towards multicultural principles. Islam as a rahmatal lil alamin religion has given serious attention to the development of education for the survival of civilized human beings in the midst of diversity. Islamic education is basically education that aims to shape the Muslim person as a whole by developing the full potential of human beings to have intellectual, spiritual, emotional and social intelligence. Islam teaches the way of life which is based on multiculturalism. Tolerant behavior, mutual respect and equal rights are one of the main prerequisites pursued in Islam for each individual to form a safe and just life order. The ability to apply multicultural values is a manifestation of true Islam. Multicultural Islamic education emphasizes a philosophy of cultural pluralism into the education system based on the principles of equality, mutual respect, tolerance, acceptance and understanding. Tolerance in diversity and moral commitment to social justice.Keywords: Conception of Islamic Education, Multicultural Principles